A Prospective, Multi‐Center, Clinical Trial of a 10‐kHz Spinal Cord Stimulation System in the Treatment of Chronic Pelvic Pain. Issue 1 (8th August 2020) - Tate, Jordan L.; Stauss, Thomas; Li, Sean; Rotte, Anand; Subbaroyan, Jeyakumar
Abstract: Background: Chronic pelvic pain (CPP) is a debilitating condition that often leads to disability and does not respond to conventional treatments. This study was conducted to evaluate the effects of paresthesia‐independent 10‐kHz spinal cord stimulation (SCS) in subjects with CPP. Methods: This prospective, single‐arm pilot study enrolled subjects with clinical diagnoses of CPP and mean pain scores of ≥ 5.0 cm on a 10‐cm VAS. Subjects underwent trial stimulations with 10‐kHz SCS, and those who had successful trial stimulations (≥40% pain relief) received permanently implanted devices and were followed for 12 months. Results: Of the 21 subjects who underwent the 10‐kHz SCS trial, 17 were successful and 14 subjects received permanent implants. No neurological deficits were observed in any subjects and all adverse events (AEs) were resolved without sequelae during the study period. Over 12 months, mean VAS scores decreased by 72% from baseline, and 10 of 13 subjects (77%) were responders (≥50% pain relief). Pain remission (VAS score ≤ 3.0 cm) was reported by 8 of 13 subjects (62%), and mean pain scores on the short‐form McGill Pain Questionnaire 2 decreased as well. Pain Disability Index scores declined by 29 points, and 85% of the subjects reported satisfaction. Conclusions: Paresthesia‐independent stimulation with 10‐kHz SCS reduced pelvic pain in subjects with CPP and was not associated with any unexpected AEs. While larger, controlled studies are needed, results of this study suggest that this therapeutic modality could potentially treat patients with CPP while improving their quality of life.